Technical Perspective hXDP: Light and Efficient Packet Processing Offload. - Zilberman, Noa (Communications of the ACM, 2022)
The article describes solutions to bridging the performance gap between CPUs (central processing units) and networks. These solutions can be either software or hardware based and include Linux’s eXpress Data Path—XDP and Field Programmable Gate Arrays—FPGA. The author suggests that by using XDP programmers will be free from learning new programming languages, design paradigms or hardware architectures.